Uji Efektifitas Beberapa Entomopatogen Pada Larva Oryctes rhinoceros L. (Coleoptera: Scarabaeidae) di Laboratorium - Ridha Hasanah Sihombing; Syahrial Oemry; Lahmuddin Lubis (Jurnal Agroekoteknologi, 2014)
Research on title The Effectivity of Some Entomopathogenic on the Larvae Oryctes rhinoceros L.(Coleoptera: Scarabaeidae) in the Laboratory". The objective of this research was to know theeffectifity of entomopathogenic (Bacillus thuringiensis, Beauveria bassiana, and Metarhiziumanisopliae) with different level of concentration. The research was conducted at the InsectLaboratory, Faculty of Agriculture, University of Sumatera Utara, From July to August 2013, usinga randomized complete design (RAL) non factorial with ten treatments (control, B. thuringiensis 25,50, and 75 g/l, B. bassiana 25,50, and 75 g/l, M. anisopliae 25, 50, and 75 g/l) with threereplications. The results showed that the highest percentage (100%) of mortality larvae in thetreatment B. thuringiensis 75 g/l and the lowest (50,71%) in B. bassiana 25 g/L. The highestpercentage (100%) of larvae infected with entomopathogenic in treatment B.thuringiensis 75 g/l, B.bassiana 75 g/l, M. anisopliae 75 g/l , and the lowest (72,93%) in treatment B. bassiana 25 g/L. Thedeath behavior of larvae O. rhinoceros infected entomopathogenic characterized by the larvaebecome slow, decreased of appetite, and have a different colors.Key Words: Oryctes rhinoceros, entomopathogenic, mortality